2016
DOI: 10.1021/acs.biochem.5b01202
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Enzymatic Activity of SETDB1 and Its 1:1 Complex with ATF7IP

Abstract: The protein methyltransferase (PMT) SETDB1 is a strong candidate oncogene in melanoma and lung carcinomas. SETDB1 methylates lysine 9 of histone 3 (H3K9), utilizing S-adenosylmethionine (SAM) as the methyl donor and its catalytic activity, has been reported to be regulated by a partner protein ATF7IP. Here, we examine the contribution of ATF7IP to the in vitro activity and substrate specificity of SETDB1. SETDB1 and ATF7IP were co-expressed and 1:1 stoichiometric complexes were purified for comparison against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…Finally, our results could provide a potential explanation for the discrepancy between two previous studies on the regulation of methyltransferase activity of SETDB1 by ATF7IP [5,34]. In both these studies, SETDB1 that was produced in insect cells was used.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Finally, our results could provide a potential explanation for the discrepancy between two previous studies on the regulation of methyltransferase activity of SETDB1 by ATF7IP [5,34]. In both these studies, SETDB1 that was produced in insect cells was used.…”
Section: Discussionmentioning
confidence: 80%
“…would be different. Thus, we speculated that the ubiquitination level of SETDB1 in the complex was higher in the ATF7IP coexpressed condition shown in the study by Wang et al [5], but not in the study conducted by Basavapathruni et al [34], and that the difference in the ubiquitination status between the two studies could be the reason for inconsistent results. In support of this idea, the addition of ATF7IP after the purification did not increase the enzymatic activity of SETDB1 in in vitro as shown in the study conducted by Wang et al [5].…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Initially, ATF7IP was proposed to act as a direct modulator of the catalytic activity of SETDB1, with mAM, the murine homolog of ATF7IP, shown to stimulate the catalytic activity of murine SETDB1 in vitro and promote the efficient conversion of di-methyl H3K9 to the tri-methylated state (Wang et al., 2003). However, a recent study found little effect of human ATF7IP on the in vitro catalytic activity of human SETDB1 (Basavapathruni et al., 2016), leading to the suggestion that the in vivo role of ATF7IP could be to regulate the spatial or temporal recruitment of SETDB1 to target sites on chromatin (Basavapathruni et al., 2016, Koch et al., 2009). …”
Section: Introductionmentioning
confidence: 99%
“…By sequence, MET-2 is most similar to vertebrate SETDB1 (Poulin et al 2005;Andersen and Horvitz 2007). Both enzymes can catalyze mono and di-methylation on H3K9, and directly or indirectly regulate H3K9me3 (Basavapathruni et al, 2016;Loyola et al, 2009;Towbin et al, 2012;Wang et al, 2003). SET domain methyltransferases contain a 'switch position' in their catalytic site that determines the degree of methylation, with bulkier residues able to accommodate mono-and di-but not tri-methylation (Jih et al, 2017).…”
Section: Distinct Roles For DI Vs Tri Methylated H3k9 In Cell Fate Pmentioning
confidence: 99%